Clinical validation of a novel enzyme-linked immunosorbent spot assay-based in vitro diagnostic assay to monitor cytomegalovirus-specific cell-mediated immunity in kidney transplant recipients: a multicenter, longitudinal, prospective, observational study - Banas, Bernhard; Sommerer, Claudia; Krämer, Bernhard; Krüger, Bernd (Transplant international, 2018)
Impaired cytomegalovirus (CMV)-specific cell-mediated immunity (CMV-CMI) is a major cause of CMV reactivation and associated complications in solid-organ transplantation. Reliably assessing CMV-CMI is desirable to individually adjust antiviral and immunosuppressive therapy. This study aimed to evaluate the suitability of T-Track® CMV, a novel IFN-γ ELISpot assay based on the stimulation of peripheral blood mononuclear cells with pp65 and IE-I CMV proteins, to monitor CMV-CMI following kidney transplantation. A prospective longitudinal multicenter study was conducted in 86 intermediate-risk renal transplant recipients. CMV-CMI, CMV viral load, and clinical complications were monitored over 6 months post-transplantation. Ninety-five percent and 88-92% ELISpot assays were positive pre- and post-transplantation, respectively. CMV-specific response was reduced following immunosuppressive treatment and increased in patients with graft rejection, indicating the ability of the ELISpot assay to monitor patients' immunosuppressive state. Interestingly, median pp65-specific response was ninefold higher in patients with self-clearing viral load compared to antivirally treated patients prior to first viral load detection (P < 0.001), suggesting that reactivity to pp65 represents a potential immunocompetence marker. Altogether, T-Track® CMV is a highly sensitive IFN-γ ELISpot assay, suitable for the immunomonitoring of CMV-seropositive renal transplant recipients, and with a potential use for the risk assessment of CMV-related clinical complications (ClinicalTrials.gov Identifier: NCT02083042).
Gesehen am 22.04.2020